2021
DOI: 10.1108/lht-01-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Let eyes tell: experimental research on university library signage system and users' wayfinding behavior

Abstract: PurposeWayfinding efficiency is an extremely influential factor to improve users' library interior experience. However, few research has studied the different functions of various wayfinding signages for university library users through mobile visual experiment. To fill this gap, the purpose of this paper is to explore the relationship between university library signage system design and patrons' wayfinding behavior features.Design/methodology/approachIn this article, an eye movement tracking method was introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Signage is a core topic in the advanced period (2016–2021). It appears that studies are focusing more on the impact of visual environmental attributes in the field [ 53 , 73 , 97 , 98 , 99 , 100 ]. In the developing period, there was a shift towards virtual reality, with novel topics such as “virtual reality” (18th), and “virtual environments” (16th) developing as leading research priorities [ 17 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signage is a core topic in the advanced period (2016–2021). It appears that studies are focusing more on the impact of visual environmental attributes in the field [ 53 , 73 , 97 , 98 , 99 , 100 ]. In the developing period, there was a shift towards virtual reality, with novel topics such as “virtual reality” (18th), and “virtual environments” (16th) developing as leading research priorities [ 17 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for the advanced period (2016–2020), new priorities included “eye-tracking” (36th), “isovist” (38th), and “Montreal Cognitive Assessment” (44th). Research using the eye-tracking method has been investigating the visual environmental factors that impact wayfinding behavior [ 73 , 74 , 86 , 97 , 101 , 102 , 103 , 104 ]. Isovists and visibility graph analyses have also been paid more attention recently in indoor wayfinding studies [ 56 , 105 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…More research studies have used new technologies, such as eye-movement-tracking devices, to study user behaviour in recent years. Su et al (2022) report a study using such a device to explore how library patrons interact with the university library signage system design. Their study used an eye-movement-tracking device to capture patrons' eye movement during their wayfinding process in the library interior.…”
Section: Wayfinding From the Users Perspective: The Connection Betwee...mentioning
confidence: 99%
“…Lawton (1996) found that, as spatial anxiety increased, the accuracy of pointing at landmarks that were not visible, decreased. There is evidence that people who are anxious tend to rely on directional signs rather than landmarks to find the way (Su et al, 2021). One of the reasons for anxiety when wayfinding may be time pressure.…”
Section: Literature Reviewmentioning
confidence: 99%